Effect of Stenochlaena palustris extract on circulating endothelial cellsMarmota caligata induced fever - Suhartono, Eko; Bakhriansyah, M.; Handayani, Rini (Indonesian Journal of Pharmacy, 2010)
Fever is increased  temperature  regulation  of  the  body.  In  the  process  is according  indirect  which  increased  of  free  radicals,  as  anion  superoxide  (•O2) and  will  trigger  oxidative  stress  happened.  Oxidative stress will effect in endothelial damaged. A celluler marker of damage the endothelium is increased number of Circulating  Endothelial  Cells (CEC).  The  aim  of  this  research  is  to valuated the influence of watery plant kalakai extract (Stenochlaena palustris)to number  of  Circulating  Endothelial  Cells  in  Marmota  caligata had  been  fever  and to calculated the average of CEC. The research is true experimental study, with Posttest-Only with Control Group Design, with 2 control group and 5 treatments group  of  each  4  Marmota  caligata. The CEC is   measured  by  Hladovec  method. Data  was  analyzed  by  using  Kruskal-Wallis  test  with confidence  rate  at  95  %. The  analyzed  results  got  p  =  0.001  (p  <  0.05)  means there  be  a  significant different  between  treatment  group.  From the  result, can  be  conclude  that  the present of watery  plant kalakai  extract is decreasing CEC in plasma of Marmota caligatafever induced.Key words: Fever, Circulating Endothelial Cells, Stenochlaena palustris